Myasthenia gravis in pregnancy: a case report - Assudani, Lata; Notwani, Ashish (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Myasthenia gravis is an autoimmune neuromuscular disorder characterized by weakness and fatigue of skeletal muscles of the face and extremities. It affects the people of both sexes and all ages, but twice as many female patients are affected as male patients. Myasthenia gravis usually strikes women in their third decade of life. Although disease course is variable, pregnant patients face risks of exacerbation, respiratory failure, adverse drug response, crisis and death. Because the severity of symptoms, as well as maternal mortality, is highest in the first 2 years following onset of myasthenia gravis, it is advisable for women to delay pregnancy for at least 2 years following diagnosis. Severity of symptoms and risk of maternal mortality is lowest 7 years after onset of the disease. We report a case of 26-year-old patient with G2P1IUFD1 at 37 weeks of gestation with myasthenia gravis.